2020
DOI: 10.3390/met10060753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Heat Treatment on the Microstructural Evolution and Mechanical Properties of Hot Isostatic Pressed 316L Stainless Steel Fabricated by Laser Powder Bed Fusion

Abstract: In this work, the microstructural features and mechanical properties of an additively manufactured 316L stainless steel have been determined. Three types of samples were characterized: (i) as printed (AP), (ii) annealing heat treated (AHT), and (iii) hot isostatic pressed and annealing heat treated (HIP + AHT). Microstructural analysis reveals that the AP sample formed melt pool boundaries with nano-scale cellular structures. These structures disappeared after annealing heat treatment and hot isostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The powder residues inside the pores suggested that this is a LOF porosity, despite their round shape and use of a higher laser power. The comparison of the mechanical properties of samples prepared by SLM under the stated conditions revealed that both yield strength and tensile strength reached higher values than Lavery, Rottger or Chadha [ 2 , 4 , 12 ] and also higher ductility. However, the ductility did not reach as high values (76%) as Puichaud states for samples of 316 L steel prepared by SLM [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The powder residues inside the pores suggested that this is a LOF porosity, despite their round shape and use of a higher laser power. The comparison of the mechanical properties of samples prepared by SLM under the stated conditions revealed that both yield strength and tensile strength reached higher values than Lavery, Rottger or Chadha [ 2 , 4 , 12 ] and also higher ductility. However, the ductility did not reach as high values (76%) as Puichaud states for samples of 316 L steel prepared by SLM [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, in the case of 316 L steel after SLM, there is always a certain proportion of porosity, and the content of which significantly depends on the used conditions [ 2 , 5 , 6 , 9 , 12 ]. Figure 13 shows the different levels of porosity in the structure of the samples prepared under different SLM conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations